ACTR-43. GENOMIC ANALYSIS OF RESPONDERS OF PHASE II TRIAL OF TEMOZOLOMIDE AND TRC-102 (BASE EXCISION REPAIR INHIBITOR) IN BEVACIZUMAB-NAÏVE GLIOBLASTOMA AT FIRST RECURRENCE. (11th November 2019) - Ahluwalia, Manmeet; Dhruv, Harshil; Fallah, Jaleh; Berens, Michael; Drappatz, Jan; Ye, Xiaobu; Lesser, Glenn; Cloughesy, Timothy; Walbert, Tobias; Holdhoff, Matthias; Peereboom, David; Nabors, Louis; et al.
Abstract: BACKGROUND: Temozolomide forms O 6 -methylguanine (O 6 mG), 7-methylguanine (N 7 mG), and 3- methyladenine (N 3 mA) DNA adducts. The O 6 mG DNA adduct is repaired by MGMT. N 7 mG and N 3 mA DNA adducts are removed by the base excision repair (BER) pathway, initiated by N- methylpurine DNA glycosolase (MPG). TRC-102 is a BER inhibitor that binds to the apurinic site created through the action of MPG. METHODS: A phase II study of adult glioblastoma in first recurrence was performed in the Adult Brain Tumor Consortium with temozolomide, 150 mg/ m 2 and TRC-102, 150 mg (1–5/ 28 days). Primary objective included radiographic response rate. Secondary objectives included safety and PFS-6. Exploratory objectives included tumor expression of N-methylpurine DNA glycosylase (MPG). The study tested hypothesis that combination therapy will achieve 30% RR. To understand the context of vulnerability to TRC102 we performed RNA sequencing on treatment naïve tissue from 7 patients. RESULTS: Nineteen patients were enrolled in first stage. Median age was 60 years (range: 48–76), 53% females, median KPS was 80 (range: 70–90). Median cycles of treatment was 2 (range: 1–12). No responses were observed. Median OS was 11.0 months (95% CI: 8–18 months), median PFS was 2.0 months (95% CI: 1.8–3.6 months). PFS-6 rate was 10.5 % (2/19). The combination was safe. MPG staining was negative in six, 1+ in five and 2+ in three patients. PFS of 11 + months in two patients (exceptional responders) was associated with MPG expression. Preliminary analysis on RNA sequencing revealed significant enrichment for DNA Damage Response pathways (MsigDB), chromosomal instability gene signature (CIN70 and CIN25), and proliferative gene signature (PCNA25) in these 2 patients. CONCLUSIONS: TRC 102 with temozolomide has acceptable safety but did not meet the primary endpoint of response. Gene signature of MsigDB, CIN70, CIN25 and PCNA25 was seen in exceptional responders and biomarker driven study is planned.